Embryonically induced β-catenin haploinsufficiency attenuates postnatal heart development and causes violation of foetal genes program - Palchevska, O.L.; Balatskii, V.V.; Andrejeva, A.O.; Macewicz, L.L.; Piven, O.O.; Lukash, L.L. (Вiopolymers and Cell, 2013)
The β-catenin role in myocardium remodeling and hypertrophy development is the subject of numerous and controversial investigations. Aim. To investigate the significance of cardiac ablation of β-catenin for heart development using conditional knockout approach. Methods. Standard histological techniques (HE- and MT-staining) and quantitative RT-PCR were used. Results. Our data demonstrate that β-catenin haploinsufficiency in heart provokes upregulation of foetal genes program without visible morphological abnormalities comparing to control groups of animals of the same age. Conclusions. Our data demonstrate that experimental conditions in this study provoke the delay in the development and growth of adult heart without visible morphological abnormalities.